2016
DOI: 10.1038/nature18930
|View full text |Cite
|
Sign up to set email alerts
|

Synchronized cycles of bacterial lysis for in vivo delivery

Abstract: The pervasive view of bacteria as strictly pathogenic has given way to an appreciation of the widespread prevalence of beneficial microbes within the human body1–3. Given this milieu, it is perhaps inevitable that some bacteria would evolve to preferentially grow in environments that harbor disease and thus provide a natural platform for the development of engineered therapies4–6. Such therapies could benefit from bacteria that are programmed to limit bacterial growth while continually producing and releasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
481
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 556 publications
(513 citation statements)
references
References 31 publications
1
481
0
3
Order By: Relevance
“…They utilize the natural colonizing properties of bacteria and viruses to deliver drug to the diseased sites. A 2016 study by Din et al showed how a clinically relevant bacterium could be engineered using tools of synthetic biology to lyse synchronously at a threshold population density and release genetically encoded anticancer cargo on demand in the required vicinity [26]. Although, natural carriers like bacteria and viruses are superior over synthetic analogs due to their inherent colonizing tendency into tumor cells, combating their immune response inside the body poses a big challenge.…”
Section: Future Perspectivementioning
confidence: 99%
“…They utilize the natural colonizing properties of bacteria and viruses to deliver drug to the diseased sites. A 2016 study by Din et al showed how a clinically relevant bacterium could be engineered using tools of synthetic biology to lyse synchronously at a threshold population density and release genetically encoded anticancer cargo on demand in the required vicinity [26]. Although, natural carriers like bacteria and viruses are superior over synthetic analogs due to their inherent colonizing tendency into tumor cells, combating their immune response inside the body poses a big challenge.…”
Section: Future Perspectivementioning
confidence: 99%
“…Others ,however ,own such potentials after getting modification in their genetic constitutions. Two examples of genetically modified bacteria to be active as cancer killer bacteria and are being briefed [15,16] in the followings; 1-Synchronizing bacterial lysing strains that have the ability of an in-vivo delivery system that grow and release cytotoxic agents insitue which acts as circuit engineered bacteria [15] .…”
Section: Class Iv: Commensal Microbiomementioning
confidence: 99%
“…Now, Din et al 1 exploit a relationship between bacteria and diseased human tissue for a therapeutic purpose. On page 81, the authors outline a system in which engineered bacteria acting as drug-delivery vehicles simultaneously break down, releasing an antitumour drug in synchronized cycles to maximize delivery efficiency and minimize toxicity.…”
Section: S H I B I N Z H O Umentioning
confidence: 99%
“…Despite these features, bacteria alone (whether engineered or not), are unlikely to eradicate tumours 1,5 . In the current study, treatment of mice with the engineered microbes in combination with chemotherapy did not destroy the tumour; instead tumours shrank for 18 days, after which regrowth occurred.…”
Section: S H I B I N Z H O Umentioning
confidence: 99%
See 1 more Smart Citation